Analisis Empiris Hubungan antara Ekspor, Impor, Nilai Tukar dan Pertumbuhan Ekonomi di Indonesia - Intan Sari Arfiani (Jurnal Ekonomi Pembangunan, 2019)
This study investigates the relationship between Export, import, exchange rate and economic growth in Indonesia. This study tries to answer the problem regarding this relationship by using Vector Autoregression (VAR) methode. From the results, it can be said that the export and import variables have a significant two-way causality relationship at the 95 percent confidence level. The export variable is significant at a 90 percent confidence level causing changes in the exchange rate variable, while the exchange rate variable significant at the 95 percent confidence level causes a change in the export variable. The exchange rate variable is also significant at the 95 percent confidence level causing changes in the economic growth variable. The shock on export variable will greatly affect import variable, and vice versa. Shock in the exchange rate variable affects all other variables in the study, while shock in economic growth variable has a small effect except for the variable itself and the exchange rate variable. From this finding, it can be seen that the exchange rate is the most crucial variable to maintain.